Mitigasi Risiko Social Engineering dan Keamanan Identitas Digital pada Ekosistem Mobile Banking melalui Edukasi Preventif bagi Siswa SMA Kota Tangerang - Abdul Rahman; Neng Wiwin; Afifah Khaerani A (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2025)
The digital transformation in the banking sector has increased financial accessibility for the younger generation, yet it has also expanded vulnerabilities to cyberattacks based on psychological manipulation. High school students, as active users of mobile banking, often become primary targets of social engineering crimes due to limited literacy regarding digital identity security. This Community Service (PkM) activity aims to enhance students' awareness and technical capabilities in mitigating digital fraud risks within the banking ecosystem. The implementation method was conducted through expert-sharing sessions based on the experience of banking IT practitioners, phishing attack simulations, and education on protecting credentials such as PINs and OTPs. The results indicated a significant increase in students' awareness of recognizing information manipulation patterns and multi-layered identity protection techniques. The final evaluation proved that this preventive education successfully changed students' digital behavior to be more vigilant, which is a crucial factor in maintaining the integrity of the digital financial ecosystem in the Tangerang City area.